Technique-economical viability of repowering of small hydroelectric power plant considering the social insert and environmental preservation - Maldonado, Oscar A. [UNESP]; Panunzio, Paulo A. [UNESP]; Silva, Dinara F. [UNESP]; Silveira, José Luz [UNESP] (My University, 2006)
The increasing growth of electrical energy demand, associated with an increase in the costs of energy production and the care related to environmental and social questions lead the planning of the world energetic sector to set a strategy for a more efficient utilization of the existing production sources. This work presents a case study of repowering a Small Hydroelectric Power Plant (SHPP), to demonstrate that this kind of enterprise is feasible in offering an augment of electrical energy to the system so to supply any future demand. Based on the statistics of a river hydraulic potential supplying the plant, one verifies the possibility of raising the capacity of electrical power generation of a water fillet in approximately 75%. The presented analysis of the technical-economical viability does not only consider the value of the equipments and the current costs of the electrical energy, but is also an effort to incorporate the various environmental and social benefits which can be obtained by the repowering of a SHPP, with emphasis to the generation and commercialization of carbon credits which enable the reduction of the investment paying-off time, making this enterprise more attractive from an economical, social and environmental standpoints.
Keywords: Carbon Credit; Electrical Generation Capacity; Repowering; Small Hydroelectric Power Plant; Social Insertion; Sustained Development